Psychometric Evaluation of a Fifth-Grade Standardized Examination: An Item Analysis of Multiple-Choice Questions - Tahir Ullah; Farzana Salim; Jawad Ali Shah (Research Mosaic, 2026)
The present research study has conducted an all-inclusive item analysis of the fifth-class standardized examination to assess its psychometric quality. To analyze the difficulty index (P) and the discriminating power (D) for fifteen MCQs, established on the answers from the higher-achievers and lower-achievers groups, the classical test theory was employed. It has been found that most of the items, i.e., 12 out of 15 MCQs, fell into the moderately difficult range (0.30<P<0.70), and three items were easy, having a P value higher than 0.70. It was also found that out of 15 items, ten items were in the “very good” discriminating category (D ≥ 0.40), while the rest of five items were either borderline or acceptable (0.20 ≤ D < 0.30) and needed valuation according to the discrimination investigation. The evaluation as a whole has an excellent reliability index value of 0.989 for distinguishing the high-scoring students from low-scoring students. This work highlights the significance of post-administration item analysis in confirming and refining classroom assessment tools.